2007
DOI: 10.1300/j067v27n01_09
|View full text |Cite
|
Sign up to set email alerts
|

The Clothesline Project

Abstract: Social workers participate with many different populations including perpetrators, victims, and survivors of domestic violence. It is crucial that students in the social work field are educated in the arena of domestic violence. The purpose of this study is to explore the effect of intimate exposure to this population through an experiential learning project, the Clothesline Project, as an enhancement to field experience and classroom instruction for MSW students. Participants included 31 female, social work g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition, the MANCOVA revealed that these attitudes and beliefs were significantly decreased as compared with students in other courses. These findings are especially important because of the demonstrated relationship between attitudes about survivors and practitioners' actual practice behaviors (Bent-Goodley, 2007;Cheek, Rector, & Davis, 2007;Tower, 2003). Thus, it is essential that we prepare social workers to enter the field to work directly or indirectly with survivors and that such preparation should promote accurate knowledge and dispel myths and stereotypes about survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MANCOVA revealed that these attitudes and beliefs were significantly decreased as compared with students in other courses. These findings are especially important because of the demonstrated relationship between attitudes about survivors and practitioners' actual practice behaviors (Bent-Goodley, 2007;Cheek, Rector, & Davis, 2007;Tower, 2003). Thus, it is essential that we prepare social workers to enter the field to work directly or indirectly with survivors and that such preparation should promote accurate knowledge and dispel myths and stereotypes about survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Various academic disciplines have demonstrated the success of experiential learning. Cheek, Rector, and Davis (2007) found that social work graduate students who integrated experiential learning into their curriculum reported enhanced knowledge and understanding in their course objectives. Similarly, gerontology social work students who took what they had learned in the classroom and applied it to their targeted population during the semester in the form of experiential learning exhibited improved understanding and confidence within their gerontology curriculum (Downey, & Miles, 2005).…”
Section: Experiential Learning Through Trainingmentioning
confidence: 98%
“…Experiential learning that contributes to social change and centers around reflection on the process provides in-vivo teaching opportunities to facilitate students' learning. Students engaged in experiential learning show increased self-awareness and improved cultural competency (Pugh, 2014), have a more nuanced understanding of the population (Cheek, Rector, & Davis, 2007), and also show a more complex understanding of, and commitment to, social justice (Cramer et al, 2012).…”
Section: Benefits Of Experiential and Service-learningmentioning
confidence: 99%